The degree of practicing teaching skills in the twenty-first century among geography teachers in Jordan from the point of view of their supervisors - Al-qudah, Nahar Diab Sobuh (Journal of Educational and Psychological Sciences, 2022)
The current study aimed to identify the degree of practice of teaching skills in the twenty-first century among geography teachers in Jordan from the point of view of their supervisors. And problem solving, classroom learning management, communication and information and communication technology, mastering education, and evaluating student learning), the study was applied by a comprehensive survey on the study population of (154) supervisors. The study concluded that the degree of practicing teaching skills in the twenty-first century among geography teachers in Jordan from the point of view of their supervisors in the total degree and fields was medium, and the results showed that there were no statistically significant differences in the degree of practicing teaching skills in the twenty-first century among geography teachers in Jordan. From the point of view of their supervisors, it is attributed to the variable of gender and educational qualification, while it was found that there were statistically significant differences due to years of experience and in favor of those with higher experience. The study recommended the necessity of urging geography supervisors for teachers to apply strategies for developing critical thinking and solving problems in teaching and learning, that the Ministry of Education hold training courses for geography teachers on teaching skills in the twenty-first century, encouraging teachers to employ authentic evaluation strategies in evaluating student learning. Such as the achievement file, and the use of questions directed to deeper learning among students.